Training Courses in Laryngeal Nerve Monitoring in Thyroid and Parathyroid Surgery- The INMSG Consensus Statement - Wu, Che-Wei; Randolph, Gregory W.; Barczyński, Marcin; Schneider, Rick; Chiang, Feng-Yu; Huang, Tzu-Yen; Karcioglu, Amanda Silver; Konturek, Aleksander; Frattini, Francesco; Weber, Frank; Liu, Cheng-Hsin; Dralle, Henning; et al. (Frontiers in Endocrinology, 2021)
Intraoperative neural monitoring (IONM) is now an integral aspect of thyroid surgery in many centers. Interest in IONM and the number of institutions that perform monitored thyroidectomies have increased throughout the world in recent years. For surgeons considering the introduction of IONM in their practice, specific training in IONM devices and procedures can substantially shorten the learning curve. The International Neural Monitoring Study Group (INMSG) has been at the forefront of IONM technology and procedural adoption since the introduction of neural monitoring in thyroid and parathyroid surgery. The purpose of this document is to define the INMSG consensus on essential elements of IONM training courses. Specifically, this document describes the minimum training required for teaching practical application of IONM and consensus views on key issues that must be addressed for the safe and reliable introduction of IONM in surgical practice. The intent of this publication is to provide societies, course directors, teaching institutions, and national organizations with a practical reference for developing IONM training programs. With these guidelines, IONM will be implemented optimally, to the ultimate benefit of the thyroid and parathyroid surgical patients.